Spittlebugs (Hemiptera: Cercopidae): Integrated Pest Management on Gramineous Crops in the Neotropical Ecozone - Espitia Buitrago, Paula Andrea; Manzano, Maria R.; Hernández, Luis M. (Frontiers in Sustainable Food Systems, 2022)
Spittlebugs (Hemiptera: Cercopidae) species cause large economic losses on gramineous crops (Poaceae) in tropical and subtropical America. These insects are key pests of sugarcane and forages, which experienced a quick expansion in extensive monocultures in Brazil, Colombia, and Mexico the last years. Projected growth in the production of meat, milk, and sugar in Latin America and the Caribbean for the next decade, along with an expected increase in the demand for these commodities in the developed countries, make necessary the mobilization towards sustainable crop and livestock systems. This profile combines information on Cercopidae taxonomy, geographical distribution, insect biology, and control strategies to contribute to the development of integrated pest management in grasses and sugarcane in the Neotropics.